The Bullseye: HST, Keck/KCWI, and Dragonfly Characterization of a Giant Nine-ringed Galaxy - Imad Pasha; Pieter G. van Dokkum; Qing Liu; William P. Bowman; Steven R. Janssens; Michael A. Keim; Chloe Neufeld; Roberto Abraham (The Astrophysical Journal Letters)
We report the discovery and multiwavelength follow-up of LEDA 1313424 (“Bullseye”), a collisional ring galaxy (CRG) with nine readily identified rings—the most so far reported for a CRG. These data shed new light on the rapid, multiring phase of CRG evolution. Using Hubble Space Telescope (HST) imaging, we identify and measure nine ring structures, several of which are “piled up” near the center of the galaxy, while others extend to tens of kiloparsecs scales. We also identify faint patches of emission at large radii (~70 kpc) in the HST imaging and confirm the association of this emission with the galaxy via spectroscopy. Deep ground-based imaging using the Dragonfly Telephoto Array finds evidence that this patch of emission is part of an older, fading ring from the collision. We find that the locations of the detected rings are an excellent match to predictions from analytic theory if the galaxy was a 10-ring system whose outermost ring has faded away. We identify the likely impacting galaxy via Keck/KCWI spectroscopy, finding evidence for gas extending between it and the Bullseye. The overall size of this galaxy rivals that of known giant low surface brightness galaxies (GLSBs) such as Malin I, lending credence to the hypothesis that CRGs can evolve into GLSBs as their rings expand and fade. Analysis of the H i content in this galaxy from ALFALFA finds significantly elevated neutral hydrogen with respect to the galaxy's stellar mass, another feature in alignment with GLSB systems.